Christian-Jewish Dialogue in the Land of Sick Imagination. On the Margins of Waldemar Chrostowski’s Book Kościół, Żydzi, Polska - Janusz Salamon, SJ (Zagłada Żydów)
The article is a polemic with the pessimistic assessment of the current state of the Christian-Jewish dialog presented by Waldemar Chrostowski in his recent book Kościół, Żydzi, Polska [The Church, Jews, Poland]. The author criticizes Rev. Chrostowski for defining the Christian-Jewish and Polish-Jewish relations in terms of strict opposition and unavoidable conflict of interests, and for putting all blame on Jews, while absolving Christians from all their past and present sins which contributed to the tensions between the two communities.